Vernacular Insurrections: Race, Black Protest, and the New Century in Composition-Literacies Studies by Carmen Kynard - Hall, Ted (Radical Teacher, 2016)
Vernacular Insurrections Race, Black Protest, and the New Century in Composition-Literacies Studies is a masterful study of race, literacy, rhetoric and composition that deserves the widest readership. Building on four decades of scholarship that reexamine the Student-led, Black Protest phase of the 1960’s movement, Vernacular Insurrections underscores the critical role of Black student organizations and the Black Arts Movement in the development of African American Literacies, Rhetorics, and Resistance.